Development of Pametra Synectics-Based E-Book to Improve Fourth Grade Students' Writing Skills - Amalia, Amalia; Panca Dewi Purwati (Ethical Lingua: Journal of Language Teaching and Literature, 2026)
This study is motivated by the low writing skills in simple texts, particularly reconstruction texts, among fourth-grade elementary school students. These difficulties are caused by struggles in developing ideas coherently, limited vocabulary, lack of self-confidence, and teacher-centered teaching methods. This development research aims to design, validate, and assess the effectiveness of the "Pametra: Panduan Menulis Teks Rekon Anak" E-Book, based on the synectics model, to improve the reconstruction writing skills of fourth-grade elementary students. The research method uses the ADDIE model (Analyze, Design, Development, Implementation, Evaluation). The research subjects consisted of students from classes IV A and B at SD Negeri Salaman Mloyo, Semarang. Data collection was carried out through observations, interviews, questionnaires, tests (pretest-posttest), and expert validation. The findings are as follows: (1) The Pametra E-Book was developed based on a needs analysis that identified students' difficulties in writing reconstruction texts, limited learning materials, and a preference for visual learning styles. (2) The product design was developed using the Canva software application, considered highly suitable based on the validation of content experts (93.75%) and media experts (91.67%). (3) The Pametra E-Book effectively improved reconstruction writing skills with an average N-Gain of 0.60 (moderate category), and the paired sample t-test results showed significance of 0.000 (p<0.05). The product implementation demonstrated improvements in understanding text structure through the "Story House" analogy, the ability to develop ideas using the adiksimba table, and the "Film Camera" analogy, as well as increased creativity, motivation, and student independence in learning. Therefore, the Pametra E-Book based on the synectics model is suitable and effective for use as an innovative learning medium to improve reconstruction text writing skills among fourth-grade elementary school students.